2017
DOI: 10.1038/s41598-017-07220-w
|View full text |Cite
|
Sign up to set email alerts
|

N-glycan mediated adhesion strengthening during pathogen-receptor binding revealed by cell-cell force spectroscopy

Abstract: Glycan-protein lateral interactions have gained increased attention as important modulators of receptor function, by regulating surface residence time and endocytosis of membrane glycoproteins. The pathogen-recognition receptor DC-SIGN is highly expressed at the membrane of antigen-presenting dendritic cells, where it is organized in nanoclusters and binds to different viruses, bacteria and fungi. We recently demonstrated that DC-SIGN N-glycans spatially restrict receptor diffusion within the plasma membrane, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 62 publications
(110 reference statements)
1
15
0
Order By: Relevance
“…A few of the fungal adhesion references document roles of glycans in adhesion. In addition to their roles in fungal glues [ 6 ] and as ligands for lectin adhesins [ 72 ], they are also necessary for biofilm cohesion [ 92 , 93 , 94 ], fungal cell binding to surfaces [ 95 ], and aggregation of adhesins [ 96 ]. β-Glucans are an essential component of the matrix in C. albicans biofilms [ 45 , 97 , 98 ], and given their prevalence in fungal cell walls and the presence of molecular machinery for their synthesis and secretion, they may well be important in other fungal biofilms.…”
Section: Structural Characteristics Of Known Fungal Cell Adhesinsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few of the fungal adhesion references document roles of glycans in adhesion. In addition to their roles in fungal glues [ 6 ] and as ligands for lectin adhesins [ 72 ], they are also necessary for biofilm cohesion [ 92 , 93 , 94 ], fungal cell binding to surfaces [ 95 ], and aggregation of adhesins [ 96 ]. β-Glucans are an essential component of the matrix in C. albicans biofilms [ 45 , 97 , 98 ], and given their prevalence in fungal cell walls and the presence of molecular machinery for their synthesis and secretion, they may well be important in other fungal biofilms.…”
Section: Structural Characteristics Of Known Fungal Cell Adhesinsmentioning
confidence: 99%
“…Two recent AFM-based papers describe indirect effects of glycans on adhesion. Host cell glycans are the subject of [ 96 ]. This paper shows that glycans of the Candida recognition receptor DC-SIGN, a mannose-specific lectin, are strengthened through glycan-mediated modulation of membrane rigidity, and subsequent stiffening of the cytoskeleton.…”
Section: Structural Characteristics Of Known Fungal Cell Adhesinsmentioning
confidence: 99%
“…Mutagenesis of its single N-glycosylation site (N80A) does not alter the expression levels and overall binding capacity nor nanocluster formation. However, unlike the wild-type receptor, the DC-SIGN-N80A mutant exhibits clathrin-independent internalization of virus particles and reduced adhesion strengthening when binding Candida albicans (Torreno-Pina et al, 2014;Te Riet et al, 2017). This could be explained by DC-SIGN-N80A inability to laterally interact with actin-anchored transmembrane glycoproteins like CD44.…”
Section: Membrane Immune Receptor Glycosylation: Beyond Protein Foldimentioning
confidence: 95%
“…Wildtype DC-SIGN diffusion pattern-but not that of DC-SIGN-N80A-indeed overlaps with that of CD44, being restricted to membrane areas of high clathrin density (Torreno-Pina et al, 2014). This interaction is possibly regulated by galectins since proteomic studies show colocalization of DC-SIGN, CD44, and Galectin-9 at the phagosome (Buschow et al, 2012), and lactose addition, which competes with binding of extracellular galectins to N-glycan chains, prevents adhesion strengthening during DC-SIGN-pathogen binding (Te Riet et al, 2017).…”
Section: Membrane Immune Receptor Glycosylation: Beyond Protein Foldimentioning
confidence: 99%
“…Adhesion strengthens with time, suggesting that the macrophage membrane engulfs the pathogen quickly after initial contact, leading to its internalization. Riet et al also found that specific receptors of dendritic cells recognizing mannan patterns in C. albicans cell wall strengthen the pathogen–host interaction and trigger the invasion through a clathrin‐dependent mechanism (te Riet et al, ; te Riet, Joosten, Reinieren‐Beeren, Figdor, & Cambi, ).…”
Section: Forces In Cellular Invasionmentioning
confidence: 99%